2019
DOI: 10.5703/1288284316880
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Load Response of Large Diameter Closed-Ended and Open-Ended Pipe Piles Installed in Alluvial Soil

Abstract: The Joint Transportation Research Program serves as a vehicle for INDOT collaboration with higher education institutions and industry in Indiana to facilitate innovation that results in continuous improvement in the planning, design, construction, operation, management and economic efficiency of the Indiana transportation infrastructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Pier 7 (an interior pier) of the bridge was selected for the live load test because a static load test on instrumented test piles ( 7 11 ) had been performed in 2016 close to this pier, providing valuable reference for the understanding of the foundation response to the live load in the present study. In addition, most of the in situ tests (standard penetration tests and cone penetration tests) had been performed close to Pier 7, and the test results can be found in ( 8 , 9 , 11 13 ). The test site consists mainly of poorly-graded sand and gravel mixtures.…”
Section: Instrumentationmentioning
confidence: 99%
“…Pier 7 (an interior pier) of the bridge was selected for the live load test because a static load test on instrumented test piles ( 7 11 ) had been performed in 2016 close to this pier, providing valuable reference for the understanding of the foundation response to the live load in the present study. In addition, most of the in situ tests (standard penetration tests and cone penetration tests) had been performed close to Pier 7, and the test results can be found in ( 8 , 9 , 11 13 ). The test site consists mainly of poorly-graded sand and gravel mixtures.…”
Section: Instrumentationmentioning
confidence: 99%
“…Manandhar et al [33] concluded that, a small increase in tapering degree of the pile affects signi cantly on a higher skin friction comparing with conventional straight piles at different sand relative densities. Other investigations studied the factors that directly affect the pile load capacity as pile geometry [16,21,22,26,49], pile material [10], pile installation technique methods [1,2,15] and soil conditions [14,45]. Due to install piles into a thick strata and di cult driving conditions, steel conical driving shoes are the preferred end closure for open-ended pipe piles.…”
Section: Introductionmentioning
confidence: 99%
“…Manandhar et al [33] concluded that, a small increase in tapering degree of the pile affects signi cantly on a higher skin friction comparing with conventional straight piles at different sand relative densities. Other investigations studied the factors that directly affect the pile load capacity as pile geometry [16,21,22,26,49], pile material [10], pile installation technique methods [1,2,15] and soil conditions [14,45]. Due to install piles into a thick strata and di cult driving conditions, steel conical driving shoes are the preferred end closure for open-ended pipe piles.…”
Section: Introductionmentioning
confidence: 99%